Efecto de la exposición a altas temperaturas sobra las pupas irradiadas de la Mosca del Mediterráneo, Ceratitis capitata - Katiyar, K.P.; Ferrer, F. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
"Irradiated (10 Kr) and normal Medfly pupae were incubated for 2, 4, 6, and 8 hours at temperatures of 25, 30, 40 and 45°C, and 60 to 85 percent relative humidity. Adult emergence was normal up to 40°C. Exposure to 45°C for two hours or longer was lethal to irradiated as well as normal pupae. A heat treatment of 40°C for 8 hours immediately after irradiation had no latent adverse effect on the longevity of the adults. Irradiated females survived longer than normal females.